Концептуальні аспекти агентного моделювання бізнес-оточення ІТ-компанії для формування портфеля проєктів - Гринченко, Марина Анатоліївна; Москаленко, Вадим Юрійович; Фонта, Наталія Григорівна (Харківський національний університет радіоелектроніки, 2023)
The purpose of this work is to model the company's business environment in order to study its changes and the influence degree on the company's functioning and the composition of the IT project portfolio. It is proposed to use multi-agent modeling to construct a behavioral models of the company's business environment in the strategic period. The company, as an agent, learns to analyze its current KPI improvement strategy and look for an effective strategy, considering the changing external business environment.
Keywords: бізнес; бізнес-оточення; агентне моделювання; ІТ-компанії; ІТ-бізнес; портфелі проєктів